Kinematic chains in ski jumping in-run posture - Janurova, E.; Janura, M.; Cabell, L.; Svoboda, Z.; Vareka, I.; Elfmark, M. (Journal of Human Kinetics, 2013)
concept of kinematic chains has been systematically applied to biological systems since the 1950s. The course of a ski jump can be characterized as a change between closed and open kinematic chains. The purpose of this study was to determine a relationship between adjacent segments within the ski jumper`s body`s kinematic chain during the in-run phase of the ski jump. The in-run positions of 267 elite male ski jumpers who participated in the FIS World Cup events in Innsbruck, Austria, between 1992 and 2001 were analyzed (656 jumps). Two-dimensional (2-D) kinematic data were collected from the bodies of the subjects. Relationships between adjacent segments of the kinematic chain in the ski jumper`s body at the in-run position are greater nearer the chain`s ground contact. The coefficient of determination between the ankle and knee joint angles is 0.67. Changes in the segments` positions in the kinematic chain of the ski jumper`s body are stable during longitudinal assessment. Changes in shank and thigh positions, in the sense of increase or decrease, are the same.